The Relationship Between Emotional Competence, Classroom Climate and School Achievement in High School Students [la Relación Entre Competencia Emocional, Clima de Aula y Rendimiento Académico en Estudiantes de Secundaria] - Oriol-Granado, X (Fundacion Infancia y Aprendizaje, 2016)
The aim of this study is, on the one hand, to find out if differences exist in emotional competence and secondary school students perceptions of classroom climate according to gender and educational level and, on the other hand, to analyse the relationship between emotional competence, classroom climate and school achievement in secondary school students. The study advances the hypothesis that emotional competences and classroom climate are mediators in school achievement. For this purpose, 420 students from secondary and further education were selected with an average age of 14.29 ± 1.52. In emotional competence, the results showed differences according to gender and educational level, while in classroom climate, differences were only found according to educational level. The mediational analysis showed that classroom climate is an influential variable in the predictive value of emotional competence in relation to school achievement. Likewise, emotional competence acts as a mediating influence on classroom climate and school achievement. This study thus highlights the need to implement training processes to help teachers to promote positive socio-emotional contexts and programmes to develop students emotional competence, which will improve their school achievement. © 2015 Fundacion Infancia y Aprendizaje.